Indicators of Research Quality - Ronald H. Nowaczyk; David G. Underwood (Arizona State University, 1995)
The move toward more public accountability of institutions of higher education has focused primarily on undergraduate education. Yet, many institutions view research as an important component of their mission. Much of the literature on assessing research quality has relied on quantitative measures such as level of outside funding and number of publications generated. Focus groups consisting of research faculty were conducted at a landgrant university. Faculty were asked to evaluate current indicators of research quality as well as to suggest additional measures. While faculty recognized the need for the traditional measures, they cautioned against over-reliance on these indicators. Additional indicators focusing on graduate education as well as external peer reviews were recommended. Developing indicators that provide evidence of long-term impact on social and scientific advancement was suggested.